DESENTRALISASI, STRATEGI BISNIS DAN KINERJA ORGANISASI - Nurjanah, Esty; Hanifah, Imam Abu (JURNAL RISET AKUNTANSI TIRTAYASA, 2017)
This study aims to examine the influence of decentralization, business strategies on organizational performance through the measurement of managerial performance. The sample in this research is 50 respondents with sampling technique by purposive sampling that is middle manager at star hotel in Banten Province. Data were collected by distributing questionnaires directly to the respondent concerned. The method of analysis used is the analysis of Structural Equation Modeling (SEM). The data in this research is processed using Smart Partial Least Square (SmartPLS) software. The results of this study revealed was decentralization affected on the organizational performance, decentralization effected on the measurement of managerial performance. Furthermore, business strategy affected on the organizational performance, business strategy affected on the measurement of managerial performance. Then, the measurement of managerial performance affected on the performance of the organization. Also, decentralization and business strategies effected on organizational performance through the measurement of managerial performance as intervening variable.Keywords: Decentralization, Business Strategy, Organizational Performance, Managerial Performance Measurement